THE INFLUENCE OF MOTIVATION, CREATIVITY, AND FAMILY ENVIRONMENT ON INTEREST IN ENTREPRENEURSHIP IN STUDENT ENTREPRENEURSHIP COMMUNITIES RIAU HIGH SCHOOL OF ECONOMICS - Nurul Sukriani; Dian Febrina; Diana Sri Dewi (Jurnal Scientia, 2022)
The purpose of this study is to determine the effect of Motivation, Creativity and Family Environment, on entrepreneurial interests among Riau of High School Economic Students. Methodology: The research method used was a survey method using a questionnaire distibuted to 35 samples. While the instrument quality testing techniques include validity and reliability tests. The classic assumption test technique uses the normality test, multicollinearity test, and heteroscedasticity test. As for testing the hypothesis using multiple linear regression analysis, t test (partial), and f test (simultaneous). Results: That only the Motivation variable has a significant effect on the Entrepreneurial Interest. Whereas Creativity And Family Environment Variables, there is no significant influence between creativity and the family environment on partiality for Entrepreneurial interest but on simultaneously, there is an influence between motiviation, creativity and family environment on entrepreneurial interests.